The ancestral hall and ancestor veneration narrative of a Huizhou lineage in Ming–Qing China - Yeqian Zhang (Journal of Asian Architecture and Building Engineering, 2023)
As a venerable institution of ancestor veneration, ancestral halls remained buildings reserved for the gentry class before the Ming dynasty, and became vehicles for transmitting a form of elitism within a privileged circle. Hence, owning ancestral halls was also deemed a manifestation of political and social status. However, among the commoner class in the Huizhou region in the Ming, numerous localized kinship organizations emerged: lineages. People were gathering strength in the communal living maintained by generations, but at the same time, they also generated a demand for common ancestor veneration to maintain lineage relationship stability. By the mid-Ming, with the surge of ancestral hall construction by lineages, the exclusive privilege of the elites for ancestral halls was broken. In Huizhou, a unique sacrificial culture with the ancestral halls as the carrier appeared. In the subsequent period of rapid economic growth, an influential new group emerged within the lineages: merchants whose increasing involvement in constructive activities allowed the ancestral hall construction to bloom, reflecting the rising status of merchants in this period. This paper focuses on such a Huizhou kinship organization, the Huang lineage, and describes the history of their ancestral hall construction in detail.